Components of the Indonesian Language and Literature Learning Curriculum - PURWANTI, Christina; PUTRAYASA, Ida Bagus; SUDIANA, I Nyoman; WISUDARIANI, Ni Made Rai (International Journal of Environmental, Sustainability, and Social Science, 2024)
Curriculum, derived from the Latin "curriculae," originally meant the distance traveled by runners and now refers to the duration of education. According to Law No. 20 of 2003, curriculum is a learning plan to achieve educational goals. In Indonesia, the curriculum is updated periodically according to developments in the era. Its main components are interrelated objectives, materials, methods, and evaluations. Ralph W. Tyler emphasizes the importance of these four aspects in understanding the curriculum, although its implementation is often complex and requires adjustment. Learning methods are the means used to achieve curriculum goals through specific procedures. Subject-centered approach: Materials come from teaching subjects and are delivered through communication between teachers and students. A student-centered approach, learning based on students' needs, interests, and abilities, with a focus on individualization. A community-oriented approach, integrating schools and communities through field trips, work experiences, and community service projects. Components of a language learning curriculum, such as objectives, methods, materials, assessments, and language skill development, are essential to ensure an effective learning process. Strong curriculum design supports optimal language growth for students